2005
DOI: 10.1246/cl.2005.250
|View full text |Cite
|
Sign up to set email alerts
|

Two Characteristic H-bonded O–H Stretching Bands for the Compounds Containing Ether Oxygen and Hydroxyl Oxygen

Abstract: The two characteristic H-bonded OH stretching bands of α-monoalkyl-ω-hydroxyorigo(oxyethylene)s, (CnEm), have been observed at about 3460 and 3330 cm−1 in the liquid state; the former is due to the localized OH···O hydrogen bonds and the latter, the OH···OH···O hydrogen bonds of chain structures. The two bands were applied to the investigation of the phase transition process from the liquid to the solid for C12E3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…In the most concentrated C 12 E 3 solutions (ϕ > 84%) inverted micelles (L 2 ) are present. The molecular structure of C 12 E 3 allows the ethylene oxide head groups to form hydrogen bonds with water as well as between each other. This network of hydrogen bonds is similar to that in poly(ethylene oxide); with increasing water concentration helical conformations are found which trap an average of 2.9 water molecules per ethylene oxide unit. , This structural motif can be found in all liquid phases as well as in the myelins. ,, The hydrocarbon chains are, especially in L α , predominantly in an all-trans configuration, except close to the headgroup. This renders the interface flexible with respect to the conformation and orientation of the chains. Studies on monolayers have shown that the interfacial area per molecule is about 0.36 nm 2 and the thickness of the monolayer is 2.3 nm, with the chain and headgroup contributing 1.25 and 1.05 nm, respectively. …”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In the most concentrated C 12 E 3 solutions (ϕ > 84%) inverted micelles (L 2 ) are present. The molecular structure of C 12 E 3 allows the ethylene oxide head groups to form hydrogen bonds with water as well as between each other. This network of hydrogen bonds is similar to that in poly(ethylene oxide); with increasing water concentration helical conformations are found which trap an average of 2.9 water molecules per ethylene oxide unit. , This structural motif can be found in all liquid phases as well as in the myelins. ,, The hydrocarbon chains are, especially in L α , predominantly in an all-trans configuration, except close to the headgroup. This renders the interface flexible with respect to the conformation and orientation of the chains. Studies on monolayers have shown that the interfacial area per molecule is about 0.36 nm 2 and the thickness of the monolayer is 2.3 nm, with the chain and headgroup contributing 1.25 and 1.05 nm, respectively. …”
Section: Introductionmentioning
confidence: 89%
“…The molecular structure of C 12 E 3 allows the ethylene oxide head groups to form hydrogen bonds with water as well as between each other. [29][30][31][32] This network of hydrogen bonds is similar to that in poly(ethylene oxide); with increasing water concentration helical conformations are found which trap an average of 2.9 water molecules per ethylene oxide unit. 33,34 This structural motif can be found in all liquid phases as well as in the myelins.…”
Section: Introductionmentioning
confidence: 92%
“…The formation progress of the gas hydrate sediments [99][100][101][102][103][104][105][106] The decomposition progress of the gas hydrate sediments [100,[102][103][104][106][107][108][109][110] Tracing gas and water transport and boundary changes…”
Section: Application Area Specific Research Content Referencesmentioning
confidence: 99%
“…The porosity and the saturation of the gas-excess artificial hernia hydrate-were tested by Jin et al [65] They found that the saturation of hernia hydrate with a porosity of 39.1% was 85.1%, and the saturation of hernia hydrate with a porosity of 53.3% was 74.2%. Furthermore, the distribution of hydrates could be observed from the images obtained from X-ray CT. [109] The methane hydrate distribution and hydrate saturation were studied in the fine sand by Seol et al [67] The initial water saturation was studied from 19% to 53%, and they found that the distribution of methane hydrate was not uniform. Using a micro-focus X-ray CT, the structure of the hydrate sediment was observed by Jin et al [64] The distribution of free gas, sand, water, and hydrate in the pores can be clearly shown in 2D CT images ( Figure 2).…”
Section: Measuring the Hydrate Saturation And Its Influence On Exploimentioning
confidence: 99%
See 1 more Smart Citation